Different Incidence and Pattern of p15INK4b and p16INK4a Promoter Region Hypermethylation in Hodgkin´s and CD30-Positive Non-Hodgkin´s Lymphomas - García, María José; Martínez-Delgado, Beatriz; Cebrián, Arancha; Martínez, Ángel; Benítez, Javier; Rivas, Carmen (Elsevier, 2002)
The p16INK4a and p15INK4b 5 CpG island hyper methylation has been described as one of the most frequent mechanisms leading to inactivation of these tumor suppressor genes in hematological malignan cies. The p16 and p15 promoter regions were studied using methylation-specific polymerase chain reaction in 53 CD30 non-Hodgkin¿s lymphomas (25 anaplastic large-cell, 13 peripheral T cell, and 15 anaplastic dif fuse large B cell) and 26 Hodgkin¿s lymphomas, with the aim of comparing the methylation status of these tumor suppressor genes in anaplastic large-cell lym phomas and other related entities. p16 and p15 meth ylation was detected, respectively, in 28% and 60% of CD30 non-Hodgkin¿s lymphomas and in 38% and 42% of Hodgkin¿s neoplasms. This confirms the p16-meth ylated status in Hodgkin¿s cases described in a single previous study and adds information concerning the p15 gene that was also found to be methylated in this lymphoma subtype. Methylation incidence within cases at diagnosis and at relapse suggests that it is an early event in anaplastic large-cell lymphomas, being involved in tumor progression in Hodgkin¿s cases. Our results show that although p16 and/or p15 meth ylation is involved in non-Hodgkin¿s and Hodgkin¿s tumors that share morphological and phenotypic fea tures, differences in incidence, pattern of methyl ation, and implication in tumor progression are ob served. (Am J Pathol 2002, 161:1007¿1013)